Metabolic accompaniment of urina lithogenicity in female rats - Viktor Flyunt; Igor-Severyn Flyunt; Walery Zukow (Kazimierz Wielki University, 2022)
Background. We have previously discovered connections between the lithogenicity index of urine and a number of components of its composition. The aim of this study is to determine the relationship between the urine lithogenicity index and a number of metabolic components of plasma. Materials and Methods. Experiment was performed on 60 healthy old female Wistar rats 220-300 g. Ten animals remained intact, using daily water from drinking ad libitum. Other animals for 6 days were loaded through the tube with daily and various mineral waters at a dose of 1,5 mL/100 g of body mass. The day after the completion of the drinking course collected daily urine and estimate its lithogenicity. We determined plasma levels of electrolytes, nitric metabolites, glucose, amylase, cholesterol and lipids peroxidation parameters. Results. The lithogenicity of urine is upregulated by the plasma level of uric acid, bilirubin, potassium, malondialdehyde and catalase, but it is downregulated by calciumemia. The rate of determination of lithogenicity is 45,7%. Conclusion. Both lithogenic and litholytic factors are present in the plasma. This gives grounds for finding ways to correct lithogenicity.